THOUGHTS OF COMPARISON OF RESONANCE FREQUENCIES OF CHEMICAL ELEMENTS OF PERIODIC TABLE WITH PERSON’S BIORHYTHMS - V. V. Butukhanov (Acta Biomedica Scientifica, 2012)
Resonance frequencies of chemical elements of periodic table were obtained for the first time, exact limits of electroencephalogram rhythms were determined, correspondence of ranges (677 — 0,02 Hz) of resonance frequencies of chemical elements with rhythms of brain, heart, breathing and intestines work and. their octaves with limits of frequencies that are resonance with frequency of hydrogen atom radiation was revealed.